Persuasive communication and tourists behavior in protected areas - Novianti, Evi; Desiana, Rahmatika (Universitas Padjadjaran, 2023)
Background: Persuasive communication has the opportunity to create and change tourist behavior to better preserve the natural environment, especially in tourism that applies sustainable concepts. Purpose: This study aims to determine the effect of persuasive communication on tourist behavior in Ir. H. Djuanda Forest Park. Methods: The method used in this research is descriptive and verification research methods, with the research approach, used being quantitative and explanatory survey methods. Primary data was obtained through observation of the Ir. H. Djuanda Forest Park and questionnaires to visiting tourists while obtaining secondary data through previous research documents, literature, and government policies. This study uses data analysis techniques with the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) by testing the hypothesis using path analysis. Results: The study shows that the better the Communicator conveys something, the more influence will be given to tourists. In addition, the better the channel the Communicator provides, the more tourist visitors will increase. Conclusion: The Communicator has a significant favorable influence on tourist behavior, which means that what is conveyed to visitors can be understood, and anything that involves deliberate efforts to change other people’s minds is called persuasive communication. The better the Communicator conveys something, the more influence will be given to tourists. Implications: This study has implications for managers of tourism destinations located in protected areas, especially for local governments, in setting policies for developing tourism destinations.